ISO standards a potential path for emerging markets: an initial literature review - Lizarzaburu, Edmundo R.; Quispe Salguero, Julio (Virtus Interpress, 2011)
Nowadays, the companies and financial institutions from emerging markets are looking forward for more space in the international market. They have found several alternatives and one of them is to implement process and procedures in order to be more efficient and offer better conditions to the local and foreign customers. One of these alternatives is to implement internal standards not only following corporate governance policies but also, implementing international standards such as ISO norms. This paper seeks to show the evolution of initial ISOs most frequently used in the financial emerging markets.
Keywords: International Standards; Normas internacionales; ISO Standards; Normas ISO; https://purl.org/pe-repo/ocde/ford#5.02.04